A quantitative analysis of the direct and indirect costs of nitrogen fixation: a model based on Azotobacter vinelandii - Inomura, Keisuke (ISME J, 2017)
Nitrogen fixation is advantageous in microbial competition when bioavailable nitrogen is scarce, but has substantial costs for growth rate and growth efficiency. To quantify these costs, we have developed a model of a nitrogen-fixing bacterium that constrains mass, electron and energy flow at the scale of the individual. When tested and calibrated with laboratory data for the soil bacterium Azotobacter vinelandii, the model reveals that the direct energetic cost of nitrogen fixation is small relative to the cost of managing intracellular oxygen. It quantifies the costs and benefits of several potential oxygen protection mechanisms present in nature including enhanced respiration (respiratory protection) as well as the production of extracellular polymers as a barrier to O(2) diffusion, and increasing cell size. The latter mechanisms lead to higher growth efficiencies relative to respiratory protection alone. This simple, yet mechanistic framework provides a quantitative model of nitrogen fixation, which can be applied in ecological simulations.